The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/1471-2148-9-70
|View full text |Cite
|
Sign up to set email alerts
|

Rapid speciation in a newly opened postglacial marine environment, the Baltic Sea

Abstract: Background: Theory predicts that speciation can be quite rapid. Previous examples comprise a wide range of organisms such as sockeye salmon, polyploid hybrid plants, fruit flies and cichlid fishes. However, few studies have shown natural examples of rapid evolution giving rise to new species in marine environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
128
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 36 publications
(43 reference statements)
3
128
1
Order By: Relevance
“…It is now widely accepted that species in the Fucus genus experienced recent radiation (Leclerc et al 1998, Serrão et al 1999, Coyer et al 2006. In recent studies, authors have tried to date these splitting events; by inferring a molecular clock, Hoarau et al (2007) recently suggested a divergence time of 10 to 16 million yr between Fucus and Ascophyllum nodosum and of 2.3 to 5.5 million yr within Fucus and Muhlin & Brawley (2009), using the same molecular clock, dated the divergence between haplotypes of F. vesiculosus between 35 000 and 65 000 yr ago, while with microsatellites, Pereyra et al (2009) estimated the time since divergence of F. radicans and F. vesiculosus around 400 yr ago (125 to 2475 yr ago) using a coalescent approach. As mentioned by Coyer et al (2006) it is not trivial to find a consensus for the species concept within the Fucus genus because of intraspecific morphological variation and frequent hybridization among taxa.…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely accepted that species in the Fucus genus experienced recent radiation (Leclerc et al 1998, Serrão et al 1999, Coyer et al 2006. In recent studies, authors have tried to date these splitting events; by inferring a molecular clock, Hoarau et al (2007) recently suggested a divergence time of 10 to 16 million yr between Fucus and Ascophyllum nodosum and of 2.3 to 5.5 million yr within Fucus and Muhlin & Brawley (2009), using the same molecular clock, dated the divergence between haplotypes of F. vesiculosus between 35 000 and 65 000 yr ago, while with microsatellites, Pereyra et al (2009) estimated the time since divergence of F. radicans and F. vesiculosus around 400 yr ago (125 to 2475 yr ago) using a coalescent approach. As mentioned by Coyer et al (2006) it is not trivial to find a consensus for the species concept within the Fucus genus because of intraspecific morphological variation and frequent hybridization among taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a number of species have thus been able to evolve local adaptations over only a few thousand years, and in one exceptional case, the rapid evolution has even resulted in the formation of a new and endemic species, F. radicans. This species originates from Baltic Sea populations of F. vesiculosus and was formed no more than a few thousand years ago (Pereyra et al 2009). …”
Section: Rapid Evolution Of Baltic Sea Populationsmentioning
confidence: 99%
“…Phenotypic plasticity allows populations to adjust within the time-scale of a generation to a minor environmental change, while the presence of genetic variation constitutes the basis for evolutionary changes resulting in differentiation among populations after a minimum of some generations. In some cases evolutionary change may even result in formation of new species, and a pertinent example of this in the Baltic Sea is the new species Fucus radicans formed within the last few thousands of years (Pereyra et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The dynamic radiation, which continues in contemporary time as evidenced by the speciation of Fucus radicans in the upper Baltic Sea within the past 2000-400 yrs (Pereyra et al, 2009), has long challenged our concepts of species and speciation, largely because of environmentally-determined morphologies and extensive hybridization among the component entities.…”
Section: Introductionmentioning
confidence: 99%
“…Habitat-driven speciation has also occurred in subtidal F. vesiculosus/F. radicans (Bergström et al, 2005;Pereyra et al, 2009).…”
Section: Introductionmentioning
confidence: 99%